Sense of Belonging in a Time of Crisis: Mapping Out the Lived Cross-Cultural Experiences of International Students During the COVID-19 Pandemic - Jianfen Chen; Yao Yang (COVID)
This study investigates the cross-cultural experiences and evolving sense of belonging among international students during the COVID-19 pandemic at a large Midwestern U.S. university. Using a mixed-methods approach, we collected quantitative data through a Qualtrics survey and qualitative insights from in-depth interviews. Findings reveal that while students generally adapted to academic and social disruptions, they faced intensified challenges related to cultural isolation, mental health struggles, and immigration uncertainties. Resilience, individualized coping strategies, and shifts in their sense of belonging emerged as key themes. The study contributes practical and theoretical insights by identifying institutional strategies to strengthen cultural inclusion, mental health support, and student engagement during global crises. These findings inform future research, university policies, and support systems aimed at enhancing international students’ wellbeing and fostering more inclusive educational environments during times of uncertainty.